Development of Algebra Test Problems Based on Minimum Competency Assessment (MCA) for Junior High School - Suryawati Suryawati; Khairul Umam; Nafisyah Laila; Ayu Mastura; Md Baharuddin bin Abdul Rahman (Universitas Syiah Kuala, 2023)
The Minimum Competency Assessment (MCA) is one of the components of the National Assessment (NA) in Indonesia, which aims to measure students' cognitive abilities, including numeracy skills. Students with low numeracy skills can be affected by not being used to working on MCA-type problems. This study aims to develop MCA items on algebra that meet valid, practical, and effective criteria using the Tessmer model, including preliminary, self-evaluation, expert reviews, one-to-one, small group, and field test stages. The subjects in this study were 36 Year 7 students of one junior high school in Banda Aceh, Indonesia. The instruments used were validation sheets, practicality sheets, and student response problemnaires. The findings indicated that 15 MCA problems on algebra have met the validity, practicality, and effectiveness criteria. It shows teachers can use MCA items to train students' numeracy skills. Future researchers are expected to develop multiple problems within a single stimulus with more varied content and context; they will need to consider the novelty of the stimulus in real conditions in the field.